SLEEP TOURISM AS A STRATEGIC MARKETING COMMUNICATION TOOL FOR ATTRACTING WELLNESS- ORIENTED TRAVELERS IN INDONESIA - Rusli Akhmad Junaedi; Mushthofa Kamal; Firda Diartika; Hablana Rizka; Tri Rafika Diyah Indartin (Laboratorium Ilmu Komunikasi Fisip UHO, 2025)
This study investigates travelers’ and hotel managers’ perceptions and experiences of sleep tourism in Indonesia as a strategic marketing tool for attracting health-oriented travelers. This research was inspired by the increasing public awareness of the importance of mental and physical health, especially after the pandemic, as demand for tourism programs that support sleep quality becomes more critical and Indonesia’s potential as a sleep tourism destination is integrated into the health tourism sector. This research used a qualitative approach with a case study design. Data collection techniques were triangulated by collecting data through in-depth interviews, observation, and documentation. The data analysis technique used was thematic analysis. The results of this study indicate that sleep tourism has significant potential in Indonesia through an emphasis on developing health tourism programs integrated with sleep tourism experiences, supported by effective marketing through digital channels to increase tourist participation in the post-pandemic health tourism segment. Further research is recommended to evaluate the impact of sleep tourism programs on traveler experience and satisfaction in more depth by exploring cross-sector collaboration